A training programme involving automatic self-transcending meditation in late-life depression: preliminary analysis of an ongoing randomised controlled trial - RETRACTED - Akshya Vasudev; Amanda Arena; Amer M. Burhan; Emily Ionson; Hussein Hirjee; Pramudith Maldeniya; Stephen Wetmore; Ronnie I. Newman (BJPsych Open, 2016)
Late-life depression affects 2–6% of seniors aged 60 years and above. Patients are increasingly embracing non-pharmacological therapies, many of which have not been scientifically evaluated. This study aimed to evaluate a category of meditation, automatic self-transcending meditation (ASTM), in alleviating symptoms of depression when augmenting treatment as usual (NCT02149810). The preliminary results of an ongoing single-blind randomised controlled trial comparing a training programme involving ASTM with a wait-list control indicate that a 12-week ASTM programme may lead to significantly greater reductions in depression and anxiety severity. As such, ASTM may be an effective adjunctive therapy in the treatment of late-life depression.